2016
DOI: 10.1080/09243453.2016.1201123
|View full text |Cite
|
Sign up to set email alerts
|

How do student and classroom characteristics affect attitude toward mathematics? A multivariate multilevel analysis

Abstract: This study investigated the effects of student and classroom characteristics on math self-confidence, perceived usefulness, and enjoyment of mathematics as multiple outcomes. A sample of 7th-grade students from 78 classes of 49 schools was studied. The data were collected using, among other instruments, an attitude questionnaire. The results of the multivariate multilevel analysis showed that the variance of the 3 indicators was situated mostly at the student level, and that the indicators correlated strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 55 publications
(65 reference statements)
3
18
1
8
Order By: Relevance
“…Multi-level modelling techniques offer tools to do this, in a fashion that is robust to missing and unbalanced data (Gelman & Hill, 2007;McElreath, 2015). Although these techniques have not yet been widely applied in the field of child language development, with the notable exception of Rowe et al (2012), they are becoming common in other fields such as education (Kiwanuka et al, 2017;Oldfield, Humphrey, & Hebron, 2017) and cognitive science (Mirman, 2016).…”
Section: Studying Language Development Across Timementioning
confidence: 99%
“…Multi-level modelling techniques offer tools to do this, in a fashion that is robust to missing and unbalanced data (Gelman & Hill, 2007;McElreath, 2015). Although these techniques have not yet been widely applied in the field of child language development, with the notable exception of Rowe et al (2012), they are becoming common in other fields such as education (Kiwanuka et al, 2017;Oldfield, Humphrey, & Hebron, 2017) and cognitive science (Mirman, 2016).…”
Section: Studying Language Development Across Timementioning
confidence: 99%
“…The findings were in line with those found by other researchers working in primary schools in developed countries in terms of the effect size of the subject. Researchers using multilevel analysis in developing countries have found that the school variances tend to be considerably higher although many of the studies suffered from limitations in designing [12]. For this Indonesian study the smaller variance results were likely to reflect the particular nature of the sample in which only urban state schools were included.…”
Section: Discussionmentioning
confidence: 84%
“…Classroom characteristics and parental attitudes are also important factors that need to be considered with respect students' mathematics learning (see e.g. Kiwanuka et al, 2017).…”
Section: Resultsmentioning
confidence: 99%